Redescription of Centronia melanitis Hübner, 1818 (Lepidoptera: Arctiinae: Arctiini: Ctenuchina) with notes on androconial organs - Grados, Juan; Mantilla, Karla (Entomological Communications, 2021)
The Neotropical genus Centronia Hübner, 1818 is monotypic and represented by the species Centronia melanitis Hübner, 1818. Individuals of this species display diurnal habits and are attracted by plant bait of Heliotropium sp.. Specimens of Centronia are very rare in museum collections. The present study, notes are provided for the male specimens and the first time the female is mentioned in the scientific literature. The presence of androconial organs in Centronia melanitis and other species of Ctenuchina is hypothesized to be related to the visits to pyrrolizidine sources and their role in the pheromones production and the sexual attraction for mating.